A retrospective study on molecular epidemiology trends of carbapenem resistant Enterobacteriaceae in a teaching hospital in Malaysia - Zhi Xian Kong; Rina N. Karunakaran; Kartini Abdul Jabar; Sasheela Ponnampalavanar; Chun Wie Chong; Cindy Shuan Ju Teh (PeerJ, 2022)
Background Carbapenem resistant Enterobacteriaceae (CRE) has rapidly disseminated worldwide and has become a global threat to the healthcare system due to its resistance towards “last line” antibiotics. This study aimed to investigate the prevalence of CRE and the resistance mechanism as well as the risk factors associated with in-hospital mortality. Methods A total of 168 CRE strains isolated from a tertiary teaching hospital from 2014–2015 were included in this study. The presence of carbapenemase genes and minimum inhibitory concentration of imipenem, meropenem and colistin were investigated. All carbapenem-resistant Klebsiella pneumoniae (K. pneumoniae) strains were characterised by PFGE. The risk factors of patients infected by CRE associated with in-hospital mortality were determined statistically. Results The predominant CRE species isolated was K. pneumoniae. The carbapenemases detected were blaOXA-48, blaOXA-232, blaVIM and blaNDM of which blaOXA-48 was the predominant carbapenemase detected among 168 CRE strains. A total of 40 CRE strains harboured two different carbapenemase genes. A total of seven clusters and 48 pulsotypes were identified among 140 CRKp strains. A predominant pulsotype responsible for the transmission from 2014 to 2015 was identified. Univariate statistical analysis identified that the period between CRE isolation and start of appropriate therapy of more than 3 days was statistically associated with in-hospital mortality.